THE INFLUENCE OF PARENTAL SOCIAL SUPPORT AND STUDENT LEARNING MOTIVATION ON SELF REGULATED LEARNING STUDENTS OF JABAL NOOR DELI SERDANG SMP IT SCHOOL - Zuraidah Harahap; Nefi Darmayanti; Hasanuddin (RADJA PUBLIKA, 2023)
This research aims to determine the influence of parental social support and student learning motivation on Self Regulated Learning of Jabal Noor Deli Serdang IT Middle School students, with a population of 300 students. The research sample consisted of 106 students. The method used in this study is a quantitative method with a sampling technique using the Random Sampling Technique. The instrument used is a Likert scale model questionnaire. The data collection technique uses three scales consisting of Parents' Social Support, Learning Motivation, and Self Regulated Learning scales. The analysis technique used is Multiple Regression. Based on the research results, it was concluded that: 1) there is a significant positive relationship between parental social support and Self Regulated Learning with a t coefficient of 2,654 with p < 0.05, and the correlation coefficient (rx1y) is 0.230 with p <0.05. 2) There is a significant positive relationship between student learning motivation and Self Regulated Learning with a t coefficient of 6,493 with p < 0.05, with a correlation coefficient (rx2y) of 0.531 with p < 0.05. 3) There is a significant positive relationship between parental support and student learning motivation with Self Regulated Learning with a coefficient F reg = 25.141 with p < 0.05, and a correlation coefficient R = 0.573 with p < 0.05 and R2 = 0.328 with a contribution of 31.5% . These results indicate that there is still 68.5% contribution from other factors that can influence Self Regulated Learning. From these results it can be said that the higher the parental support and learning motivation, the higher Self Regulated Learning,